2015
DOI: 10.1021/acs.biochem.5b00874
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phosphatidylcholine and Calcium on Self-Association and Bile Salt Mixed Micellar Binding of the Natural Bile Pigment, Bilirubin Ditaurate

Abstract: Recently [Neubrand, M. W., et al. (2015) Biochemistry 54, 1542-1557], we determined a concentration-dependent monomer-dimer-tetramer equilibrium in aqueous bilirubin ditaurate (BDT) solutions and explored the nature of high-affinity binding of BDT monomers with monomers and micelles of the common taurine-conjugated bile salts (BS). We now investigate, employing complementary physicochemical methods, including fluorescence emission spectrophotometry and quasi-elastic light scattering spectroscopy, the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A previous study suggested that lower BA content results in lower solubility of unconjugated bilirubin, promoting its precipitation. [30][31][32] Simply, decreased BA content induces the recruitment of unconjugated bilirubin, thereby contributing to brown pigment gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that lower BA content results in lower solubility of unconjugated bilirubin, promoting its precipitation. [30][31][32] Simply, decreased BA content induces the recruitment of unconjugated bilirubin, thereby contributing to brown pigment gallstone formation.…”
Section: Discussionmentioning
confidence: 99%